2020
DOI: 10.1002/chem.202000064
|View full text |Cite
|
Sign up to set email alerts
|

Iron Biomineral Growth from the Initial Nucleation Seed in L‐Ferritin

Abstract: X-ray structures of homopolymerich uman L-ferritin andh orse spleen ferritin weres olved by freezing protein crystals at different time intervals after exposure to a ferric salt and revealed the growth of an octa-nuclear iron cluster on the inner surface of the protein cage with ak ey role played by some glutamate residues.A na tomic resolution view of how the clusterf ormation developss tarting from a( m 3 -oxo)tris[(m 2 -glutamato-kO:kO')](glutamato-kO)-(diaquo)triiron(III) seed is provided. The results supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 20 publications
2
32
0
Order By: Relevance
“…Recent structural evidence, showed that three of these glutamates, namely, Glu60, Glu61 and Glu64 are responsible for anchoring oxo-centered tri-iron(III) clusters on the internal cage surface of HuLf, whereas the fourth glutamate, Glu57, is mainly involved in shuttling the incoming iron ions towards the cluster (Figure 13). [5,6] The position of the Fe5-A site observed in hMTF matches the position of one of the ferric ions (Fe2 in Figure 13) composing the trinuclear cluster in the mineralization site of HuLf.…”
Section: Insights In the Ferroxidase Process Of Hmtf In Comparison With Other Vertebrate Ferritinssupporting
confidence: 52%
See 3 more Smart Citations
“…Recent structural evidence, showed that three of these glutamates, namely, Glu60, Glu61 and Glu64 are responsible for anchoring oxo-centered tri-iron(III) clusters on the internal cage surface of HuLf, whereas the fourth glutamate, Glu57, is mainly involved in shuttling the incoming iron ions towards the cluster (Figure 13). [5,6] The position of the Fe5-A site observed in hMTF matches the position of one of the ferric ions (Fe2 in Figure 13) composing the trinuclear cluster in the mineralization site of HuLf.…”
Section: Insights In the Ferroxidase Process Of Hmtf In Comparison With Other Vertebrate Ferritinssupporting
confidence: 52%
“…The asymmetric unit of hMTF crystals includes a single protein chain, representing the spatial and time average of all protein subunits, as reported previously. [4][5][6]10] Depending on the iron-diffusion time, the structures of hMTF include a variable number of metal ions [Mg(II) and/or Fe(II)/(III) ions] whose chemical nature was discriminated according to the detected anomalous diffraction signal. Iron ions are characterized by a strong signal in the anomalous difference Fourier map determined from data collected with X-ray energy of ~7130 eV (Fe K-edge peak) that disappeared in the map computed from the data collected at energy immediately below this edge.…”
Section: Time-lapse Crystallographic Studies Of Hmtfmentioning
confidence: 99%
See 2 more Smart Citations
“…Nucleation of inorganic minerals in the presence of (bio)macromolecules increasingly attracts research attention owing to the possibility of progression toward controlling the synthesis of advanced materials and the understanding of biomineralization processes. Iron (oxy)(hydr)oxides are important (bio)-minerals [1], and their nucleation and crystal growth are closely related to the presence of bio-macromolecules in natural systems [2][3][4]. There are multiple roles that additives can play, while it has already been well established that nucleation in the presence of some additives, especially in the early stages of mineralization, cannot be satisfactorily explained from the viewpoint of classical nucleation theory [5].…”
Section: Introductionmentioning
confidence: 99%